Acid-catalyzed deuterium exchange in Hantzsch-type dihydropyridines - Kocjan, Darko (Acta chimica slovenica, 1998)
An interesting case of the acid-catalayzed deuterium exchange in methanol-d, was found for 4-phenyl-1,4-dihydropyridine derivatives that belong to the class of Ca-channel antagonists. Deuterium exchange of the C-alpha-methyl protons indicates formation of an enamine carbocation that can be described by three mesomeric models.
Keywords: derivati; heterociklične spojine; kemijske reakcije; organska kemija; organske spojine; piridin